Collaborative solutions for inter terminal transport. Issue 21 (2nd November 2017) - Gharehgozli, Amir Hossein; de Koster, René; Jansen, Rick
Abstract : Major ports contain multiple container terminals, sea terminals, train, truck and barge terminal, and empty container depots, operated by different companies. Port authorities try to streamline inter terminal container transport (ITT) within congested port areas by offering expensive common road and rail infrastructure. Alternatively, individual stakeholders can set up private or collaborative container transport systems. This paper develops a framework to analyse and determine feasibility conditions of a common ITT system in a port area, depending on total transport volumes. First, we develop a simulation model to evaluate the costs of transporting containers using different modes of transport including trucks, automated guided vehicles, and multi trailer systems. Next, the required number of vehicles per mode is determined for a given throughput and waiting time. The results of the simulation are used in a game-theoretic setting to determine the cost savings per stakeholder operating in a coalition. By comparing cost savings for all possible coalitions, it is possible to determine, for each stakeholder, the attractiveness of using a common system. We find the coalitions that result in the highest savings and compare them with the infrastructure cost required to realise them. We apply the method to determine the feasibility of a common ITT system for terminals in the Port of Rotterdam and show that it only pays off in case of high demand for container transports.